Routine screening of harmful microorgansims in beach sands should be implemented: implications to public health - Brandão, João (2014)
Beaches worldwide provide recreational opportunities and economic industry to hundreds of millions of people. Beach water is often monitored for microbiological quality to detect the presence of indicators of human sewage contamination so as to prevent public health outbreaks associated with water contact. However, growing evidence suggests that beach sand can harbor microbes harmful to human health, often in concentrations greater than the beach water. Currently, there are no standards for monitoring, sampling, analyzing, or managing beach sand quality. In addition to indicator microbes, growing evidence has identified pathogenic bacteria, viruses, and fungi in a variety of beach sands worldwide. During a workshop of experts that convened in Lisbon, Portugal, it was determined that 1) beach sand should be screened for a variety of pathogens harmful to human health, and monitoring should then be initiated alongside water monitoring; 2) sampling and analysis protocols should be standardized to allow comparisons among beach locations; and 3) further studies are needed to estimate human health risk with exposure.